2010
DOI: 10.1093/eurheartj/ehq395
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of non-invasive multidetector computed tomography coronary angiography to detect coronary artery disease using different endpoints: detection of significant stenosis vs. detection of atherosclerosis

Abstract: A total of 100 patients underwent CTA followed by both CCA and IVUS. Only those segments in which IVUS imaging was performed were included for CTA and quantitative coronary angiography (QCA) analysis. On CTA, each segment was evaluated for significant stenosis (defined as ≥ 50% luminal narrowing), on CCA significant stenosis was defined as a stenosis ≥ 50%. Second, on CTA, each segment was evaluated for atherosclerotic plaque; atherosclerosis on IVUS was defined as a plaque burden of ≥ 40% cross-sectional area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Coronary CTA has been demonstrated to be accurate for the detection of non-obstructive CAD and coronary atherosclerosis when compared to coronary intravascular ultrasound [15]. Detection of nonobstructive CAD, which may be considered an unique feature of CCTA among other non-invasive imaging modalities, has relevant prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary CTA has been demonstrated to be accurate for the detection of non-obstructive CAD and coronary atherosclerosis when compared to coronary intravascular ultrasound [15]. Detection of nonobstructive CAD, which may be considered an unique feature of CCTA among other non-invasive imaging modalities, has relevant prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that CAD patients with high calcium score have more vulnerable plaque components [8,11] (such as higher burden with calcium or presence and extent of the necrotic core within the plaques) than those with low calcium score [4,10,12].Our study results showed that patients with acute coronary syndrome and high calcium score had low attenuation voluminous plaque. Diff erent cut-off value of plaque density: 30 HU, 60 HU, 100 HU showed the same change if we assessing patients with calcium score below or above than 400, 600, 1000: the culprit lesion plaque mainly is composed by low attenuation (<30 HU) substance, the p value being statistical signifi cant in all three groups.…”
Section: Discussionmentioning
confidence: 52%
“…Some investigators believe that calcium stabilizes the plaque, this information is based on some results that showed that in stable angina the calcium score is higher than in acute coronary syndrome [6,10]. It was suggested that CAD patients with high calcium score have more vulnerable plaque components [8,11] (such as higher burden with calcium or presence and extent of the necrotic core within the plaques) than those with low calcium score [4,10,12].Our study results showed that patients with acute coronary syndrome and high calcium score had low attenuation voluminous plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Based on lipid deposition, fibrous cap thickening, lipid pool transition into necrotic core, calcium deposition, plaque disruption, haemorrhage and thrombosis, a number of categories of coronary atherosclerotic lesions have been identified and reported in Table 1 (Stary et al 1994;Virmani et al 1999;Virmani et al 2000;. Present status of CT technology clearly indicate that its diagnostic accuracy for the detection of the presence of atherosclerosis is superior over the detection of significant stenosis ultimately suggesting a progressive shift of this technique in the future towards the study of the atherosclerotic process per se rather than to simply assess the stenosis severity (Van Velzen et al, 2011). Table 1.…”
Section: B-mode Ultrasound and Ccsmentioning
confidence: 99%